Intervarietal Hybridization in Anthurium Andreanum Linden - Renu R S (Department of Plant Breeding and Genetics, College of Agriculture, 1999)
The present study on evaluation of morphological characters and compatibility reactions among ten selected Anthurium andreanum varieties, was undertaken to analyse the scope for genetic improvement in this crop. The analysis of variance revealed significant variation among the ten varieties for the twelve quantitative characters studied. This reveals the high genetic potential for the improvement of this crop. Variability studies indicated that high phenotypic and genotypic coefficients of variation for the characters plant height, position of candle, days to initiation of female phase, number of days in female phase and spathe size. The characters with heritability coupled with high genetic advance values were plant height, spathe size, spathe-candle ratio, position of candle, number of flowers per candle and days to initiation of female phase, indicating additive gene action. Plant height was found to be positively correlated with number of leaves or spadices per year. Spathe size and candle length were positively correlated. Candle length had high positive genotypic correlation with position of candle and number of flowers per candle. Pollen fertility ranged from 42 per cent in Liver Red to 13.7 per cent in Mauritius Orange. Study of pollen emergence pattern revealed significant differences among the varieties. Pollen emergence was completely absent in Pompon Red, Nitta Orange and Midori Green during the period of study. Pollen production was high in the cooler months of October to December and